An integrative approach to assess ecological risks of surface water contamination for fish populations. (January 2017) - Santos, Raphael; Joyeux, Aude; Besnard, Aurélien; Blanchard, Christophe; Halkett, Cédric; Bony, Sylvie; Sanchez, Wilfried; Devaux, Alain
Abstract: Contamination of aquatic ecosystems is considered as one of the main threats to global freshwater biodiversity. Within the European Water Framework Directive (EU-WFD) a particular attention is dedicated to assess ecological risks of surface water contamination and mitigation of chemical pressures on aquatic ecosystems. In this work, we evaluated ecological risks of surface water contamination for fish populations in four EU-WFD rivers through an integrative approach investigating three Lines of Evidence (chemical contamination, biomarker responses as early warning signals of contamination impacting individuals and ecological analyses as an indicator of fish community disturbances). This work illustrates through 4 case studies the complementary role of biomarkers, chemical and ecological analyses which, used in combination, provide fundamental information to understand impacts of chemical pressures that can affect fish population dynamics. We discuss the limitations of this approach and future improvements needed within the EU-WFD to assess ecological risk of river contamination for fish populations. Graphical abstract: Highlights: Integrated approach improve ERA implemented within the EU-WFD. Chemistry, biomarkers and ecological analyses are complementary LOE. Biomarkers point out biological disturbances before fish community are disturbed. Chemical, Biomarker and Ecological indexes improve decision making by managers.